2016
DOI: 10.1017/jfm.2016.228
|View full text |Cite
|
Sign up to set email alerts
|

Particle-resolved direct numerical simulation of homogeneous isotropic turbulence modified by small fixed spheres

Abstract: A statistically stationary homogeneous isotropic turbulent flow modified by 64 small fixed non-Stokesian spherical particles is considered. The particle diameter is approximately twice the Kolmogorov length scale, while the particle volume fraction is 0.001. The Taylor Reynolds number of the corresponding unladen flow is 32. The particle-laden flow has been obtained by a direct numerical simulation based on a discretization of the incompressible Navier-Stokes equations on 64 spherical grids overset on a Cartes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 57 publications
3
45
0
Order By: Relevance
“…This method has been used to calculate the force on a single, fixed particle in decaying homogeneous isotropic turbulence [7, 24]. Very recently this method has been applied to analyze homogeneous isotropic turbulent flow around an array of 64 fixed spherical particles [111] with a size equal to twice the Kolmogorov length and a particle volume fraction of 0.001. Extension of this method to moving particles is not straightforward due to collisions that occur and lead to overlap of the spherical grid of one particle with another particle.…”
Section: Introduction: Overview Of Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method has been used to calculate the force on a single, fixed particle in decaying homogeneous isotropic turbulence [7, 24]. Very recently this method has been applied to analyze homogeneous isotropic turbulent flow around an array of 64 fixed spherical particles [111] with a size equal to twice the Kolmogorov length and a particle volume fraction of 0.001. Extension of this method to moving particles is not straightforward due to collisions that occur and lead to overlap of the spherical grid of one particle with another particle.…”
Section: Introduction: Overview Of Simulation Methodsmentioning
confidence: 99%
“…Also, the way in which the two-way coupling force should be applied in point-particle simulations can be found from particle-resolved simulations. An example of this can be found in the recent paper on particle-resolved DNS of the flow around a fixed array of particles in homogeneous isotropic turbulence by Vreman [111]. There it was found that the agreement with point-particle DNS can substantially be improved by distributing the two-way coupling force in the point-particle DNS over a larger volume than usually chosen.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Glowinski et al developed a distributed Lagrange multiplier/fictitious domain method (DLM/FDM), and Turek et al and Wan and Turek presented a finite element fictitious boundary method (FE‐FBM) to solve particulate flow problems. Recently, Vreman applied the overset grid method to study particle‐laden pipe flows . This method is based on two sets of background meshes, ie, a fixed mesh for fluid and a body‐fitted mesh for each particle.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Vreman applied the overset grid method to study particle-laden pipe flows. 12,13 This method is based on two sets of background meshes, ie, a fixed mesh for fluid and a body-fitted mesh for each particle. In Vreman's works, the velocities and pressures on different background grids are coupled by third-order Lagrange interpolations.…”
mentioning
confidence: 99%